The least developed countries ... report - United Nations Conference on Trade and Development. Secretariat (New York United Nations, 2004)
The report provides a comprehensive and authoritative source of socio-economic analysis and data on the world´s most impoverished countries and is intended for a broad readership of governments, policy makers, researchers and all those involved with LDCs´ development policies.
Each issue has also distinctive title. Supplements: "Overview" 1998, 2006
Keywords: Economic development; ECONOMIC CONDITIONS; INTERNATIONAL ECONOMIC RELATIONS; INTERNATIONAL TRADE; REPORTS; LEAST DEVELOPED COUNTRIES